2016
DOI: 10.24105/ejbi.2016.12.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Students' Behavior Related to Oral Health

Abstract: Introduction: Oral health significantly affects the quality of life. Behavior is a very important determinant of oral health, which is related to oral hygiene, diet, regular visits to the dentist and smoking. Students are interesting research group to study an oral-helath behavior, particularly dental students, because of their knowledge and attitudes about oral health greatly affect the proceedings in their further work which is important for the health of the population. Objective: The objective was to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…11.5% (26) of the respondents reported that sometimes they feel ashamed because of the teeth problems and 0.9% (2) of participants reported periodically problems of the shame caused by teeth. At the same time, 88.5% (201) participants never avoid encounters due to problems with their teeth, mouth, or dentures, 3.5% (8) respondents sometimes avoid encounters because of the problems with their teeth, mouth, or dentures, while 6.2% (14) rarely have the same problem. Table 8 summarizes results of the importance of oral health.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11.5% (26) of the respondents reported that sometimes they feel ashamed because of the teeth problems and 0.9% (2) of participants reported periodically problems of the shame caused by teeth. At the same time, 88.5% (201) participants never avoid encounters due to problems with their teeth, mouth, or dentures, 3.5% (8) respondents sometimes avoid encounters because of the problems with their teeth, mouth, or dentures, while 6.2% (14) rarely have the same problem. Table 8 summarizes results of the importance of oral health.…”
Section: Resultsmentioning
confidence: 99%
“…Similar research was carried out in Turkey and Montenegro. In Turkey, only 12% of respondents attend their dentists regularly (13), while in Montenegro 54.4% of respondents visit the dentist every 3-6 months (14). A result from our study is in consonance with the results of the study conducted in Foča where 51% of school children visit a dentist only when they have a problem (15), and with the results found in Greece, where 51.25% of the respondents visit a dentist when they start feeling dental pain (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation